Moving Forward With the Past: History and Identity in Marie-Célie Agnant’s La Dot de Sara - Kennedy M. Schultz (Studies in 20th & 21st Century Literature, 2012)
Francophone writers and theorists have long worked to establish a cultural identity true to their collective past and free of Western authority and influence. They reflect in their works the need to find their own voice and validate their own perspective in the face of a history fraught with colonial influence and domination. Marie-Célie Agnant, a Francophone writer of Haitian descent living in Montreal, addresses this search for history and identity through the lens of Haitian immigrant characters in her works, namely La Dot de Sara (1995), Le Livre d’Emma (2001), and Un alligator nommé Rosa (2007). Agnant’s works treat the questions of identity and belonging through the experiences of her characters who are exiled from their native roots. Past histories must be recovered, transmitted and often translated repeatedly in order to maintain a connection to one’s cultural identity and history. This re-visioning of their past history and identity, however, often conflicts with the daily lives of her characters, interfering with their adjustment to their new host culture and preventing them from fully participating in contemporary society. The quandary of preserving a connection to the past while participating in modern society reveals itself most poignantly in La Dot de Sara.
Keywords: Francophone writers; Francophone voice; Francophone perspective; Marie-Célie Agnant; La Dot de Sara; Le Livre d’Emma; Un alligator nommé Rosa; questions of identity; identity; belonging; native roots; exile; cultural identity; cultural history; re-visioning of the past; modern society